Antimicrobial efficacy of Syzygium cumini leaf mouthwash following non-surgical periodontal therapy in gingivitis subjects: a clinico microbiological study - Vanaki, Bhagyashri N.; Kokatnur, Vijayalaxmi M.; Kalburgi, Nagaraj B.; Hugar, Shruti; Roy, Anjaly; Hiremath, Jayadev N. (International Journal Of Community Medicine And Public Health, 2025)
Background: Gingivitis is an inflammatory condition of the gingival tissue caused by bacterial infection and by the microbial plaque deposits located in or close to the gingival sulcus. Syzygium cumini commonly known as jamun/jamlang possesses antioxidant, anti-inflammatory, antidiabetic and antibacterial properties and can be used as reasonably safe alternative to synthetic pharmaceuticals. The leaves of jamlang have the ability to inhibit the growth of Gram negative and Gram positive bacteria. Therefore, this study aimed to assess the impact of antimicrobial efficacy of jamlang leaves in gingivitis subjects. Methods: A total of 40 gingivitis subjects were selected and divided randomly into 2 groups. Group 1- non surgical periodontal therapy alone (20), group 2- non surgical periodontal therapy followed by Syzygium cumini mouthwash (20). The supragingival plaque samples of both the groups were collected at baseline and 21 days after scaling. Simplified oral hygiene index, gingival index, plaque index and bleeding on probing were recorded at baseline and 21st day. Results: Significant reduction in clinical parameters and colony count of Porphyromonas gingivalis was seen in both the groups. But comparatively Syzygium cumini mouthwash group showed more reduction in BOP and inflammation when compared with group 1. Conclusions: Leaf extract of Syzygium cumini mouthwash showed reduction in various clinical parameters and the colony count of Porphyromonas gingivalis. Hence Syzygium cumini mouthwash can be used as an adjunct to the mechanical periodontal therapy.